1998
DOI: 10.1097/00001888-199801000-00018
|View full text |Cite
|
Sign up to set email alerts
|

An update on biostatistics requirements in U.S. medical schools

Abstract: While efforts have been made to incorporate innovative instructional techniques into these courses, most still follow the traditional lecture format and make minimal use of computers. Nevertheless, medical students appeared to have a favorable attitude toward these courses at over half of the schools surveyed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Some statisticians have called for the teaching of statistical concepts only or mainly [22][23][24] ; others have proposed analytical and computational contents in addition 25,26 . Viewed chronologically, the latter proposition is generally a more recent trend.…”
Section: Resultsmentioning
confidence: 99%
“…Some statisticians have called for the teaching of statistical concepts only or mainly [22][23][24] ; others have proposed analytical and computational contents in addition 25,26 . Viewed chronologically, the latter proposition is generally a more recent trend.…”
Section: Resultsmentioning
confidence: 99%
“…Hewett and Porpora [24] reported their experience in a course in which the students are not only taught with the aid of computerized lessons, but they have to do an entire project, including data analysis, similar to what has been found in our study. Looney et al [14] found that most of the courses in medical schools in the US were lectures, with little or no use of computers, even though most of the medical students found that computerized statistics would be more useful to them. Medical students themselves [5,6] do understand the need to learn biostatistics, a theme that was also shown in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Looney et al [14] found that although most medical students reported that computerized statistics would be helpful, most courses in U.S. medical schools were in the form of lectures, with little or no use of computers.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The community medicine module exists in the curriculum of most of the medical colleges throughout the world but with great variation regarding duration and contents. For instance in the majority of medical schools in the USA, the module includes biostatistics, epidemiology, preventive medicine, demography, and medical informatics, which are taught during the first or second study year.…”
Section: Introductionmentioning
confidence: 99%